Winter flock coherence in Willow Tits – who decide what and why - Hogstad, Olav (Ornis Norvegica, 2009)
Willow Tits Poecile montana (Parus montanus) spend the non-breeding season in mixed-age flocks consisting most often of one social dominant adult mated pair that remain in their territory for the whole of their lives, together with two or four subordinate unrelated first-year birds that have settled after a post-natal dispersal. Since the adults expel the subordinates from the safer parts of the trees in term of predation, juveniles forage in more favourable microhabitats after the flocks temporarily have split into age-specific sub-flocks. However, due to the effect of many eyes, each individual may spend less time scanning for predators and more time foraging when being in a big flock rather than in a small one. To find whether adults or juveniles initiate the splitting into agespecific sub-flocks and set the flock coherence, I followed 6-10 different flocks yearly over nine winters. Independent of ambient temperature, adult Willow Tits were the first to leave the flock when foraging in the same tree more often than juveniles, whereas juveniles left the flock more often in mild weather (≥6 °C) than in cold (<6 °C). When the adult left the flock first, juveniles followed the adult more often in cold than in mild weather, more frequently so within 12 hours than later. After being split into adult and juvenile flocks, the juveniles moved towards and accompanied adults, not the other way round. Juveniles apparently applied for adult company and mostly decided the flock size. When one of the adults left the flock first, its mate followed as the second bird more often than any of the other flock members. In mild weather, when adult and juveniles foraged in separate sub-flocks, dominant adults had no influence on the behaviour of the juveniles that foraged mostly in the upper half of pines, an area supposed to be less exposed to predators. When in company with adults and differing in space use, the juveniles used more time for vigilance and less for foraging than adults, but did not differ in foraging and vigilance time without the company of the alpha pair. Although company of dominant adults may be disadvantageous for the subordinate juvenile flock members, juveniles capitalize on the greater experience of the adults and provide more time to foraging due to a greater anti-predation benefit due to vigilance reduction because of the effect of many eyes. However, most important: because the habitat is probably saturated with dominant territory owners, flock membership of juveniles is the main route to territory ownership and probably their only chance to breed at the site the following spring. Juvenile Willow Tits that do not succeed in achieving a flock membership during summer and autumn, may leave the area and take part in long-distance movements, settle in a suboptimal habitat or live as floaters that switch among several flocks, alternatives apparently being fatal.